2019
DOI: 10.1080/25765299.2019.1628689
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of metallic reinforcements for mechanical performance enhancement in metal matrix composites: a review

Abstract: The growing application of metal matrix composites (MMCs) in structural and reliability critical applications has placed higher premium on good combinations of strength, ductility and toughness, in which ceramic reinforced MMCs currently face limitations. Metallic reinforcements have hence come under consideration as replacements of ceramics due to their good wettability and inherent ductility and toughness. This review covers the use of metallic reinforcements in Al, Mg, Cu and Zn-Al metal matrices and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…K K Alaneme et al found that the yield strength has increased by 0.2% when the Magnesium matrix is added with nickel particulates. However, the ductility is found to have decreased [42].…”
Section: Yield Strengthmentioning
confidence: 93%
“…K K Alaneme et al found that the yield strength has increased by 0.2% when the Magnesium matrix is added with nickel particulates. However, the ductility is found to have decreased [42].…”
Section: Yield Strengthmentioning
confidence: 93%
“…This improvement maybe associated to the load transfer from the Ti matrix to the relatively harder Nb 2 O 5 particles. It is also linked to increased particle and dispersion strengthening offered by the Nb 2 O 5 particles, which serve as barriers to dislocation motion [30].…”
Section: Hardness and Reduced Elastic Modulus Of The Cp Ti And Ti-nb2mentioning
confidence: 99%
“…Metal matrix composite materials came into existence in the mid to late 1970, and rapidly its demands increased in engineering industries [1,2]. MMCs possess excellent comprehensive properties such as corrosion resistance, small thermal expansion coefficient, and impact resistance, thermal and electrical conductivity [3,4].…”
Section: Introductionmentioning
confidence: 99%